Bridge Capacity Assessment through LRFR Method and Bridge Seismic Performance Evaluation Using the PBSD Concept: Case Study - Sabara, Akhmad Ilham Ramadhan; Imran, Iswandi (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
In this study, a comprehensive evaluation was conducted of the condition and performance of a concrete arch-type bridge located in close proximity to a fault. Utilizing the LRFR capacity assessment method and seismic performance analysis through the NLTHA process based on the PBSD concept, finite element modeling (FEM) was employed with a focus on construction stage analysis and model updating for calibration to site conditions. The assessment encompassed the determination of the rating factor for structural elements under service and ultimate limit state loading. Performance analysis under seismic loads includes an examination of engineering demand parameters such as concrete and reinforcement strains in columns, subjected to varying seismic hazard levels. Additional scrutiny involves assessing bearing displacement and overturning potential to identify potential damage before column failure. The primary objective of this research was to investigate pertinent and efficient techniques for evaluating bridge capacity and seismic performance. A thorough understanding of these methods is expected to facilitate the identification of suitable solutions to enhance the safety and reliability of bridges in Indonesia.